Isatuximab plus pomalidomide and dexamethasone in patients with relapsed/refractory multiple myeloma according to prior lines of treatment and refractory status: ICARIA-MM subgroup analysis. (May 2021) - Bringhen, Sara; Pour, Ludek; Vorobyev, Vladimir; Vural, Filiz; Warzocha, Krzysztof; Benboubker, Lotfi; Koh, Youngil; Maisnar, Vladimir; Karlin, Lionel; Pavic, Michel; Campana, Frank; Le Guennec, Solenn; et al.
Highlights: In ICARIA-MM, isatuximab-pomalidomide-dexamethasone (Isa-Pd) improved PFS in RRMM. We assessed Isa-Pd versus Pd in RRMM by prior lines of therapy/refractory status. Isa-Pd improved PFS in RRMM regardless of prior lines of therapy/refractory status. Isa-Pd improved ORR in RRMM regardless of prior lines of therapy/refractory status. Overall safety profile of Isa-Pd is manageable in RRMM patients. Abstract: Patients with relapsed/refractory multiple myeloma (RRMM) experience several relapses, and become refractory to successive therapies. In the ICARIA-MM trial (NCT02990338), isatuximab plus pomalidomide-dexamethasone prolonged median progression-free survival (PFS) in patients with RRMM. This subgroup analysis of ICARIA-MM assessed the treatment benefit of isatuximab by prior lines of therapy and refractory status. A total of 307 patients were randomized to isatuximab-pomalidomide-dexamethasone (n = 154) or pomalidomide-dexamethasone (n = 153). Isatuximab (10 mg/kg intravenously) was given weekly in the first 28-day cycle, then every other week. Standard pomalidomide-dexamethasone doses were given. PFS was assessed by prior lines and refractory status. Overall, 102 (66 %) patients receiving isatuximab-pomalidomide-dexamethasone and 101 (66 %) patients receiving pomalidomide-dexamethasone had received 2–3 prior lines; 52 (34 %) and 52 (34 %) had received >3 prior lines, respectively. Median PFS was higher with isatuximab-pomalidomide-dexamethasone versus pomalidomide-dexamethasone for patients who received 2–3 prior lines of therapy (12.3 vs. 7.8 months) and >3 prior lines of therapy (9.4 vs. 4.3 months). Median PFS was higher with isatuximab-pomalidomide-dexamethasone versus pomalidomide-dexamethasone for patients who were lenalidomide-refractory (11.4 vs. 5.6 months), lenalidomide-refractory at last line (11.6 vs. 5.7 months), refractory to a proteasome inhibitor (PI) (11.4 vs. 5.6 months), and double-refractory (11.2 vs. 4.8 months). Overall response rate (ORR) in patients receiving isatuximab-pomalidomide-dexamethasone versus pomalidomide-dexamethasone was 59.0 % versus 31.4 % in lenalidomide-refractory; 60.2 % versus 32.2 % in PI-refractory; and 58.6 % versus 29.9 % in double-refractory patients. Isatuximab-pomalidomide-dexamethasone improved PFS and ORR regardless of prior lines of therapy or refractory status, consistent with the benefit in the overall population.